2017
DOI: 10.3727/096504016x14732772150389
|View full text |Cite
|
Sign up to set email alerts
|

miR-422a Inhibits Glioma Proliferation and Invasion by Targeting IGF1 and IGF1R

Abstract: Glioma is a common type of malignant brain tumor characterized by aggressive metastasis capability. Recent evidence has suggested that noncoding RNAs, including microRNAs, have important functions in the pathophysiology of glioma development. In this study, we investigated the biological function of miR-422a in human glioma. We found that miR-422a was downregulated in glioma tissues. We also demonstrated that expression of miR-422a in glioma cells markedly suppressed cell proliferation, migration, and invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…Previous studies from our group and other groups have shown that miR-422a is abnormally expressed in GBM and may act as a tumor suppressor in GBM (35,38,46). Unlike common screening microarrays in which tumor tissues and ANT are selected randomly, we selected 3 paired GBM tissues with low miR-422a expression and not regulated by methylation.…”
Section: Construction Of the Circrna Network In Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from our group and other groups have shown that miR-422a is abnormally expressed in GBM and may act as a tumor suppressor in GBM (35,38,46). Unlike common screening microarrays in which tumor tissues and ANT are selected randomly, we selected 3 paired GBM tissues with low miR-422a expression and not regulated by methylation.…”
Section: Construction Of the Circrna Network In Gbmmentioning
confidence: 99%
“…In recent years, our group has focused on the role of brain-enriched miRNAs, such as miR-422a, in GBM (35). Other groups have shown that miR-422a plays crucial roles in head and neck squamous cell carcinoma, squamous cell lung cancer, and glioma pathology (36)(37)(38). However, very little is known about miRNAs related to the upstream regulators of GBM; these miRNAs may block tumorigenesis and function as molecular targets in GBM treatment.…”
Section: Introductionmentioning
confidence: 99%
“…miRs execute their functions by binding to sequences in 3′‐untranslated regions (UTR) of target mRNAs (Anglicheau, Muthukumar, & Suthanthiran, ). Several miRs have been described in relation to glioma migration and invasion, activating or inhibiting different pathways (Cui et al, ; Wang et al, ; Zhu, Zhao, Rao, & Xu, ).…”
Section: Malignant Alterations Of Glioma Cells Increase Their Invasionmentioning
confidence: 99%
“…Accumulating studies in the past decades have proved that miRNAs can act as tumor suppressors or cancer‐promoting factors in the development of HCC . miR‐422a is abnormally expressed in colorectal cancer, glioma, head and neck squamous cell carcinoma, and counts in the proliferation and metastasis of cancer cells . Importantly, miR‐422a is downregulated in HCC, and overexpression can significantly inhibit the malignant phenotypes of HCC cells .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 miR-422a is abnormally expressed in colorectal cancer, glioma, head and neck squamous cell carcinoma, and counts in the proliferation and metastasis of cancer cells. [20][21][22] Importantly, miR-422a is downregulated in HCC, and overexpression can significantly inhibit the malignant phenotypes of HCC cells. 23 While the mechanism of miR-422a dysregulation in HCC needs further investigation.…”
Section: Introductionmentioning
confidence: 99%